ARCHETYPE OF AMAZING MAN AS SEEN IN PARARATON - Handoko, Putut; Tantri Suryawati, Cicilia; Pujimahanani, Cahyaningsih (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
The research deals with the archetype of Amazing Man in Pararaton. The theory of archetype, Pararaton, amazing and a qualitative research design are applied in this research. It is found out that Ken Angrok is regarded as Amazing Man. The archetype of Amazing Man as seen in a Pararaton is that firstly, Ken Angrok is the son of god Brahma; secondly, Ken Angrok is the reincarnation of god Visnu; thirdly, Ken Angrok shines twice; fourthly, from his crown of Head, the bats can comes out; fifthly, he can kill the powerful Tunggul Ametung; sixthly, he marries Ken Dedes; seventhly, god Shiva chooses him as the king in Java, and finally, Ken Angrok becomes the king of Singasari entitled Sri Rajasa Batara Sang Amurwabumi.